Ultrasonic Characterization of Ibidi μ-Slide I Luer Channel Slides for Studies With Ultrasound Contrast Agents - Pakdaman Zangabad, Reza (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2023)
Understanding and controlling the ultrasound contrast agent (UCA)'s response to an applied ultrasound pressure field are crucial when investigating ultrasound imaging sequences and therapeutic applications. The magnitude and frequency of the applied ultrasonic pressure waves affect the oscillatory response of the UCA. Therefore, it is important to have an ultrasound compatible and optically transparent chamber in which the acoustic response of the UCA can be studied. The aim of our study was to determine the in situ ultrasound pressure amplitude in the ibidi μ -slide I Luer channel, an optically transparent chamber suitable for cell culture, including culture under flow, for all microchannel heights (200, 400, 600, and [Formula: see text]). First, the in situ pressure field in the 800- [Formula: see text] high channel was experimentally characterized using Brandaris 128 ultrahigh-speed camera recordings of microbubbles (MBs) and a subsequent iterative processing method, upon insonification at 2 MHz, 45° incident angle, and 50-kPa peak negative pressure (PNP). Control studies in another cell culture chamber, the CLINIcell, were compared with the obtained results. The pressure amplitude was -3.7 dB with respect to the pressure field without the ibidi μ -slide. Second, using finite-element analysis, we determined the in situ pressure amplitude in the ibidi with the 800- [Formula: see text] channel (33.1 kPa), which was comparable to the experimental value (34 kPa). The simulations were extended to the other ibidi channel heights (200, 400, and [Formula: see text]) with either 35° or 45° incident angle, and at 1 and 2 MHz. The predicted in situ ultrasound pressure fields were between -8.7 and -1.1 dB of the incident pressure field depending on the listed configurations of ibidi slides with different channel heights, applied ultrasound frequencies, and incident angles. In conclusion, the determined ultrasound in situ pressures demonstrate the acoustic compatibility of the ibidi μ -slide I Luer for different channel heights, thereby showing its potential for studying the acoustic behavior of UCAs for imaging and therapy